The death of German firms: What role for foreign direct investment? - Chiara Franco; John P. Weche Gelubcke (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2013)
This paper aims at examining the role played by inward Foreign Direct Investments (FDI) in affecting the exit probabilities of German manufacturing firms in the precrisis year 2007. We introduce two main novelties: in the first place, we include the FDI variable, dividing it between types of foreign investor (industrial vs. financial) besides the usual analysis with the division by country of origin. Secondly, we analyze whether FDI may have effects not only on the probability that a firm exits the domestic market, but also on whether it stops being internationally involved, that is, whether it stops importing or exporting. We find that German firms in most cases suffer from higher competition introduced by foreign firms except when they are part of a high-R&D region or a high-tech sector when they have the needed absorptive capacity to take advantage of possible spillover effects. We also find that U.S. FDI has a crowding out effect for firms located in low-tech sectors but not in high-tech sectors. The results are reversed when considering financial investments instead of industrial investments. Finally, we find that FDI is negatively correlated with exits from export markets but positively with those from import markets.
Keywords: F23; L60; O30; 330; MNE; FDI; foreign ownership; survival; Germany